DIFFUSION INDUCED GRAIN-BOUNDARY MIGRATION IN THIN GOLD COPPER-FILMS - Grovenor, C (1985)
Au/Cu thin film bimetallic couples containing well defined tilt grain boundaries have been annealed in situ to observe the phenomenology and kinetics of DIGM and DIR. The discontinuous nature of the migration process has been directly observed and correlated with changes in the mobility of the grain boundaries with misorientation. The variations in the phenomenology of DIGM/DIR with increasing temperature are discussed, and some results of other workers reinterpreted in the light of new concepts of the nucleation process of DIR, and the possibility of high temperature DIGM. © 1985.